2009
DOI: 10.1111/j.1540-8175.2008.00881.x
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐Left Atrial Mechanical Delay Detected by Tissue Doppler Echocardiography Can Be a Useful Marker for Paroxysmal Atrial Fibrillation

Abstract: This study shows an increase in intra-left atrial mechanical delay in PAF patients. This method can be used as an early marker to detect PAF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 19 publications
4
56
0
Order By: Relevance
“…Tissue Doppler echocardiography may be used for this purpose because of its high temporal and spatial resolution. We found that ILCT detected by tissue Doppler echocardiography was higher in patients with lone paroxysmal AF compared to healthy control group [14]. There was no statistically significant difference in intra-right atrial and interatrial conduction times between the groups, and only ILCT was detected as an independent marker of paroxysmal AF in that study [14].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Tissue Doppler echocardiography may be used for this purpose because of its high temporal and spatial resolution. We found that ILCT detected by tissue Doppler echocardiography was higher in patients with lone paroxysmal AF compared to healthy control group [14]. There was no statistically significant difference in intra-right atrial and interatrial conduction times between the groups, and only ILCT was detected as an independent marker of paroxysmal AF in that study [14].…”
Section: Discussionmentioning
confidence: 60%
“…We found that ILCT detected by tissue Doppler echocardiography was higher in patients with lone paroxysmal AF compared to healthy control group [14]. There was no statistically significant difference in intra-right atrial and interatrial conduction times between the groups, and only ILCT was detected as an independent marker of paroxysmal AF in that study [14]. Merckx et al [15] demonstrated that tissue Doppler echocardiography can be used to measure total duration of atrial electrical activation which is valuable to detect patients with risk of AF development.…”
Section: Discussionmentioning
confidence: 65%
“…Specifically, greater atrial mass shortens the refractory period and delays conduction, which may increase the quantity of daughter wavelets. Deniz et al (26) suggested that TDI may be used to measure inter- and intra-atrial mechanical delays and that TDI may indicate an increase in left atrial electromechanical delay in PAF patients. Also, Ariyarajah et al (27) proposed that an interatrial block on ECG may be a novel predictor of embolic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Deniz et al [30] demonstrated an increase in intra-left atrial mechanical delay in PAF patients and this delay was an independent risk factor for PAF. den Uijl et al [31] demonstrated relationship between PA lateral and late recurrence of AF.…”
Section: Intra-left Aemd P Wave Dispersion Ilct Pa Lateralmentioning
confidence: 99%